Simulasi Pengaruh Pengoperasian Filter Aktif Shunt Terhadap Kenaikan Efisiensi Transformator di RSUD Kabupaten Klungkung - A A Gede Agung Brama Dinanta; I Wayan Rinas; Anak Gede Maharta Pemayun (Program Studi Teknik Elektro UNUD, 2019)
The high level of harmonics found in the use of electrical energy can cause the system's power quality to get worse. the voltage and currentqwaveforms ofra distorted system giveerise to aneincrease inplosses that affect the efficiency0of the transformer. In this studyqa currenteTHD analysis will be carried out in Klungkung District Hospital. The simulation results will be compared with the IEEE 519-2014 standard in theconditions existing and the conditions at the operationeof the shunteactiveyfilter,analysis is alsoecarried out losses before and after the harmonics are affected. The results of theanalysis of Losses the existing conditions are losses of Phase R2.310 kW, Phase S of 2.363 kW, Phase T of 2.285 kW. The operating simulation of activefilters shunt obtained losses for phase R 2,141 Kw, Phases S 2,158 kW, Phase T 2,142 kW, so that the losses totalat the time of the existing amounted to 6,958 kW and after installation of active filters losses were total6,441 kW. The level of efficiency transformer in hospitals whenKlungkung existing amounted to 96.18% and after being fittedactive filter shuntefficiency of 96.46%.